2007
DOI: 10.1080/10635150601109759
|View full text |Cite
|
Sign up to set email alerts
|

From Phylogenetics to Phylogenomics: The Evolutionary Relationships of Insect Endosymbiotic γ-Proteobacteria as a Test Case

Abstract: The increasing availability of complete genome sequences and the development of new, faster methods for phylogenetic reconstruction allow the exploration of the set of evolutionary trees for each gene in the genome of any species. This has led to the development of new phylogenomic methods. Here, we have compared different phylogenetic and phylogenomic methods in the analysis of the monophyletic origin of insect endosymbionts from the gamma-Proteobacteria, a hotly debated issue with several recent, conflicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 86 publications
(129 reference statements)
2
23
0
Order By: Relevance
“…This dataset was previously used by Comas et al . [21] for their phylogenomic study on the monophyletic origin of insect endosymbionts from the γ -Proteobacteria, a debated issue with several conflicting reports. In addition, we used the phylogenetic tree constructed by Comas et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dataset was previously used by Comas et al . [21] for their phylogenomic study on the monophyletic origin of insect endosymbionts from the γ -Proteobacteria, a debated issue with several conflicting reports. In addition, we used the phylogenetic tree constructed by Comas et al .…”
Section: Resultsmentioning
confidence: 99%
“…[21] based on concatenated sequences of 60 homologous proteins as a reference tree (Figure 1) and compared the genome tree obtained by our OGtree2 (Figure 2) to those phylogenetic trees predicted by BPhyOG (Figure 3) [8] and our previous OGtree (Figure 4) [15]. As was argued in [21], the phylogenetic tree in Figure 1 can be considered as a good reference tree because it coincides with the taxonomy accepted by biologists for these Proteobacteria. In particular, the three Buchnera species in this reference tree form a monophyletic group with the other insect endosymbionts of B. floridanus and W. glossinidia .…”
Section: Resultsmentioning
confidence: 99%
“…However, they provide no information on how closely the reconstructed tree resembles the true evolutionary relationships of the analyzed species. Currently, the only way to reenforce phylogenetic hypotheses is the analysis of complementary data (e.g., Comas et al 2007). If the phylogenetic placement of a taxon remains stable over different data sets and different tree reconstruction methods, it is likely to reflect the true evolutionary relationships of this taxon.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenomic analyses (Delsuc et al 2005; Telford 2007) use the phylogenetic signal integrated over many genes as a proxy for the species phylogeny (Gatesy and Baker 2005; Comas et al 2007). It is hoped that this approach reduces the influence of gene-specific signals (noise) and accentuates the phylogenetic signal generated by the evolutionary relationships of the species.…”
Section: Introductionmentioning
confidence: 99%
“…The family (and order) itself has a complicated evolutionary history; while it is nominally within the gamma-proteobacteria, its relationship to that group is not straightforward. Phylogenies generally depict the lineage as splitting from the rest of the gamma-proteobacteria, and a gene-bygene analysis has revealed that many genes are more similar to genes of the alpha or beta proteobacteria, implying that much of the genome was acquired from these other lineages and the placement within gamma-proteobacteria may not be reliable (Comas et al 2007). …”
Section: Comparative Sequence Analysismentioning
confidence: 99%